Security enhancement on IEEE 802.11ad wireless networks - Huang, Kun (2017)
The development of multi-gigabit IEEE 802.11ad networks has further popularized WLAN in personal and enterprise environment and sped up the transition from wired network to wireless network. However, its key distribution mechanism, namely the 4-way handshake, is identi ed to be insecure against Denial of Service attack and does not achieve Perfect Forward Secrecy. This report thus proposed a Secure 2-Way Handshake (S2WH), to address such vulnerabilities. Instead of using two nonces, as in the original 4-way handshake, the proposed protocol utilizes hash function and one additional keying material to provide mutual authentication between the station and access point and derive a session key for subsequent data transmission. The S2WH was veri ed by both logic and automatic analyzing tool to be more secure than the original 4-way Handshake protocol. Its performance in terms of time delay and energy consumption was also compared with the original 4-way handshake, as well as some existing solutions.